La coopération intercommunale en France et au Brésil, analyse suivant l'approche de Michael Mann - Juliana Nunes Rodrigues (L'Espace Politique)
This paper focuses on practices of inter-municipal cooperation taking place in France and in Brazil. The intention is to reflect about the increase of the local scale’s strength in societies with distinct conceptions about the role of the State and about its mechanisms of social control. On the one hand, the aim is to underscore the processes of formation and diffusion of inter-municipal cooperative structures occurring in Brazil and in France by considering their dissimilar institutional arrangements. On the other hand, we want to raise the theoretical framework developed by Michael Mann, who brings innovative features to enhance analysis in the field of Political Geography. Finally, we derive a set of issues that arise in the two countries and broaden the debate on the opportunities and barriers to inter-municipal cooperation in two very different models of state.